Analysis of the relationship between indebtedness and some macroeconomic variables in Iraq - Abdul Hussien Oudah, Adnan Mohammed Hasan, Sadq Zwer Lglag, (Opción, 2019)
The unit root test of Augmented Dicky Fuller and the Phillips-Peron test were used to test the stability of time series and to find out the degree of integration between indebtedness and some macroeconomic variables in Iraq. As a result, the model used does not have a self-correlation between residues. The null hypothesis states that there is no sequential correlation between residues. In conclusion, the ratio of external debt to exports in Iraq was within the limits allowed by international comparisons.